Structural changes in endocrine pancreas of male Wistar rats due to chronic cola drink consumption. Role of PDX-1. - Gabriel Cao; Julián González; Juan P Ortiz Fragola; Angélica Muller; Mariano Tumarkin; Marisa Moriondo; Francisco Azzato; Manuel Vazquez Blanco; José Milei (PLoS ONE)
Aim The objective of this work was to analyze the structural changes of the pancreatic islets in rats, after 6 month consuming regular and light cola for 6 months. Also, we have analyzed the possible role of PDX-1 in that process. Finally, with the available knowledge, we propose a general working hypothesis that explains the succession of phenomena observed. Previously, we reported evidence showing that chronic cola consumption in rats impairs pancreatic metabolism of insulin and glucagon and produces some alterations typically observed in the metabolic syndrome, with an increase in oxidative stress. Of note It is worth mentioning that no apoptosis nor proliferation of islet cells could be demonstrated. In the present study, 36 male Wistar rats were divided into three groups to and given free access to freely drink regular cola (C), light cola (L), or water (W, control). We assessed the impact of the three different beverages in on glucose tolerance, lipid levels, creatinine levels and immunohistochemical changes addressed for the expression of insulin, glucagon, PDX-1 and NGN3 in islet cells, to evaluate the possible participation of PDX-1 in the changes observed in α and β cells after 6 months of treatment. Moreover, we assessed by stereological methods, the mean volume of islets (Vi) and three important variables: the fractional β -cell area, the cross-sectional area of alpha (A α-cell) and beta cells (A β-cell), and the number of β and α cell per body weight. Data were analyzed by two-way ANOVA followed by Bonferroni's multiple t-test or by Kruskal-Wallis test, then followed by Dunn's test (depending on distribution). Statistical significance was set at p<0.05. Cola drinking caused impaired glucose tolerance as well as fasting hyperglycemia (mean:148; CI:137-153; p<0.05 vs W) and an increase of in insulin immunolabeling (27.3±19.7; p<0.05 vs W and L). Immunohistochemical expression for PDX-1 was significantly high in C group compared to W (0.79±0.71; p<0.05). In this case, we observed cytoplasmatic and nuclear localization. Likewise, a mild but significant decrease of in Vi was detected after 6 months in C compared to W group (8.2±2.5; p<0.05). Also, we observed a significant decrease of in the fractional β cell area (78.2±30.9; p<0.05) compared to W. Accordingly, a reduced mean value of islet α and β cell number per body weight (0.05±0.02 and 0.08±0.04 respectively; both p<0.05) compared to W was detected. Interestingly, consumption of light cola increased the Vi (10.7±3.6; p<0.05) compared to W. In line with this, a decreased cross-sectional area of β-cells was observed after chronic consumption of both, regular (78.2±30.9; p<0.05) and light cola (110.5±24.3; p<0.05), compared to W. As for, NGN3, it was negative in all three groups. Our results support the idea that PDX-1 plays a key role in the dynamics of the pancreatic islets after chronic consumption of sweetened beverages. In this experimental model, the loss of islets cells might be attributed to autophagy, favored by the local metabolic conditions and oxidative stress.